Improving Students’ Learning Outcomes Using 5E Learning Cycle Model - Fauziah Rahmawati; Yani Achdiani; Shinta Maharani (ASEAN Journal of Science and Engineering Education, 2021)
Quality control of agricultural products is one of the study programs in the vocational school that applies online learning during the COVID-19 pandemic. The implementation of online learning in grade XI quality control has constraints, in which the average learning outcomes are still gaining at a low value of 58.06 in the analysis proximate material. At the time of observation, 70% of students did not understand the topic. Some students get difficulties in discovering or constructing a solution to a problem. Thus, an appropriate learning model is needed to improve student's learning outcomes. The purpose of this study was to determine the implementation of the learning cycle 5E model and discovery learning also to identify the differences in student learning outcomes between both models’ performance in the materials applying fresh milk quality standards. The research was conducted using the quasi-experimental (experiment classes used the learning cycle 5E model and control class used the discovery learning model). This study proved good analysis results. The application of the learning cycle 5E shows better results to the discovery learning model to improve student learning outcomes as evidenced by the fact that the average value of experiment classes is higher than that of the control class. The N-gain value of the experiment class is greater than that of the control class. Therefore, the learning cycle 5E model can improve students' learning outcomes.